(untitled) (Journal of Bio-Science, 2009)
A field experiment was carried out to study the influence of sowing times on yield and yield components of barley (Hordeum vulgare L.). Seeds of four barley cultivars (BB 1, Karan 19, Karan 163 and Karan 351) were sown with four sowing times (5 November, 17 November, 29 November and 11 December). Most of the yield and yield components were significantly highest in 17 November sowing. Among the cultivars most of the characters showed their highest values in BB 1 and the lowest in Karan 19. Harvest index was found highest in Karan 351 and lowest in BB 1. Key words: Barley, Sowing time, Yield. Â doi: 10.3329/jbs.v15i0.2154 Â J. bio-sci. 15: 139-145, 2007